Pemodelan Pengaruh Sektor Keuangan Terhadap Pertumbuhan Ekonomi Di Indonesia - Sutrisno, Hadi; Nuryadin, Muhammad Rusmin (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2024)
The financial sector has a major influence on economic growth in Indonesia. Good modeling influences the accuracy of economic growth predictions and has an impact on the financial sector. Several models have been introduced to analyze the relationship between the two, but it is necessary to test which of these models is most appropriate. This research aims to find the best model of the financial sector's influence on economic growth in Indonesia. Three models were compared so that the best model was selected, namely the Bayesian Vector Autocorrelation (BVAR), Linear Regression, and Pseudo Poisson Maximum Likelihood (PPML) models. The comparison method was carried out to determine the best model from the third model using various criteria, and then an in-depth study of the best model was carried out by considering various diagnostic tests and stability tests. The analysis results show that the BVAR (2) model is the best model among the three existing models. However, some specific analysis results in the regression analysis model (such as the negative impact on CPS) and the PPML model (such as the high R-square) can be taken into consideration by policyholders in the financial sector in determining policies related to these areas for economic growth.